An atomistic perspective on the diffusion and permeation of hydrogen and isotopes through an engineered nanoporous silica membrane using molecular dynamics simulations. Issue 11 (10th August 2022) - Sahu, Pooja; Ali, Sk. Musharaf
Abstract : Silica membrane for the storage and transportation of H2 and its isotopes. Abstract : Non-equilibrium molecular dynamics (NEMD) simulations were conducted for hydrogen permeability and diffusion through amorphous silica membrane to assess its suitability for the safe storage and transportation of hydrogen and its isotopes. A new methodology has been proposed to prepare the amorphous SiO2 structure by controlling the attractive interaction parameter of Si–O and O–O, which generates a silica membrane of the desired density with uniform porosity and a glass-like structure. Silica with a density of 1.0 g cm −3 and higher have a pore size of about 2–4 Å. The results show silica density higher than 1.3 g cm −3 for the storage of hydrogen gas owing to a very low permeation (of the order 10 −6 mol m −2 s −1 Pa −1 ). Interestingly, a transition from Knudsen-like permeation to activated molecule sieving-like permeation was noted while increasing the silica density from 1.0 g cm −3 to 1.3 g cm −3 . The temperature dependence of permeability as well as diffusivity confirmed the molecular sieving-like permeation of H2 through silica with a density of 2.0 g cm −3 with the activation energy of 8.5 kcal mol −1 and 9.12 kcal mol −1 for permeability and diffusivity, respectively. Subsequently, the linear relationship of permeation with pressure reflected the liquid-like stream line permeation of hydrogen through a membrane of density 2.0 g cm −3 . Besides, considering the importance of hydrogen and its isotopes' permeance in fusion research reactors, the studies were also extended to examine the permeation of hydrogen isotopes and their mixtures through SiO2 membrane. The results confirm similar activated thermal transport and streamline-like flux profiles for other H2 isotopes with the highest permeability for hydrogen over tritium as per the inverse mass relation.